2016
DOI: 10.1590/1807-1929/agriambi.v20n4p308-315
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of a Haplustalf soil under irrigation with treated wastewater and nitrogen fertilization

Abstract: The objective of this research was to investigate the effects of irrigation with treated wastewater and nitrogen (N) fertilization on the chemical characteristics of a Haplustalf soil cultivated with cotton. An experiment was conducted in a greenhouse in a completely randomized design with four replicates, and arranged in a 5 x 4 factorial. Five doses of N fertilization (0, 45, 90, 135 and 180 kg ha-1) and four sources of irrigation water (freshwater, wastewater treated by an anaerobic reactor, wastewater trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(46 reference statements)
2
8
0
1
Order By: Relevance
“…In CP2, the variables that contributed most were NO 3 − , K, S, Na, and pH, corresponding to those with higher modulus in the respective axes of the graph of Figure 3(a). Depth of soil solution collection; 2 treatments evaluated: SI: no irrigation; E20: treated domestic sewage applied at 0.20 m; E40: treated domestic sewage applied at 0.40 m; A20: surface reservoir water applied at 0.20 m; A40: surface reservoir water applied at 0.40 m. 3 Coefficient of variation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In CP2, the variables that contributed most were NO 3 − , K, S, Na, and pH, corresponding to those with higher modulus in the respective axes of the graph of Figure 3(a). Depth of soil solution collection; 2 treatments evaluated: SI: no irrigation; E20: treated domestic sewage applied at 0.20 m; E40: treated domestic sewage applied at 0.40 m; A20: surface reservoir water applied at 0.20 m; A40: surface reservoir water applied at 0.40 m. 3 Coefficient of variation.…”
Section: Resultsmentioning
confidence: 99%
“…Soil is a dispersed, polyphase, and heterogeneous system and, due to its physical, chemical and biological attributes, it allows the deposition of wastewater acting as a scrubber through the interception of suspended solids and nutrient removal [1]. e presence of residual water in the soil through the irrigation of plants alters its chemical characteristics [2,3], which can lead to possible toxicity problems depending on the concentration of the chemical elements present in the effluent [4]. Accumulation of salts may occur in the soil [5][6][7], as well as the contamination of surface and underground water sources [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been carried out to verify updates to crop yields and various attributes of soil irrigated with TSE, such as the electrical conductivity (EC), sodium level (Na), pH, organic matter and others (Duarte et al, 2008;Sandri et al, 2009;Oliveira et al, 2016;Urbano et al, 2015;Silva et al, 2016;Malafaia et al, 2016;Sandri and Rosa, 2017;Soothar et al, 2018). Thus, studies indicate that one must be careful when using TSE in plant cultivation, especially with plants sensitive to saline soils.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the great potential of TSE for agricultural use, if used improperly it can be harmful to the irrigation system, soil, plant, water resources and users. For example, Silva et al (2016) found that when using treated sewage in irrigation there was a greater accumulation of micronutrients, potassium and sodium in the soil in relation to water of the public supply system, increasing the risks of sodification. Tunc and Sahin (2015) reported that soil chemical, physical and hydraulic properties can be significantly affected by irrigation with wastewater.…”
Section: Introductionmentioning
confidence: 99%